Concise approach for the synthesis of the tetracyclic framework of Lycibarbarines A and B - Shet, Manoj N.; Nechooli, Hemanth K.; Ramana, Chepuri V. (Tetrahedron Letters, 2023)
A simple approach for the construction of the tetracyclic spiroketal skeleton of Lycibarbarine A and B has been described. Employing a solvent free condition for epoxide opening with tetrahydroquinoline as a key reaction to couple both the fragments, an oxidation followed by TBAF-mediated silyl deprotection spiroketalization establishes the complete tetracyclic core present in these natural products. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D -Glyceraldehyde; Tetracyclic spiroketal; Total synthesis